The 2-phase case-control design: an efficient way to use expert-time - Pascal Wild; Walter Schill; Eve Bourgkard; Karsten Drescher; Maria Gonzalez; Christophe Paris (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: The objective of this paper is to show the benefits of using a 2-phase case-control (2PCC) design in identifying dose-response relationships between cumulative occupational exposure as assessed by experts and lung cancer incidence in an actual study. METHODS: A population-based case-control study including 246 cases and 531 controls was conducted in an area with high lung cancer rates in Northeast France. Detailed occupational and personal risk factors were obtained in face-to-face interviews. Cumulative expert-based exposure scores were obtained from a subset of 215 cases and 269 controls stratified on smoking and a prior algorithmic exposure score for asbestos, crystalline silica, and polycyclic aromatic hydrocarbons (PAH) in the framework of a 2PCC design. This subset deliberately under-sampled large strata among controls but not among cases. Logistic regression models adapted to 2PCC studies were applied and corresponding computations of attributable fractions and their confidence intervals developed. RESULTS: Based on this 2PCC design, statistically significant dose-response relationships were obtained for asbestos, crystalline silica, PAH, and diesel motor exhaust. Simulations within this study showed that 2PCC studies were always more powerful than random samples. CONCLUSION: The 2PCC design may be the design of choice when resources allow only a limited number of subjects with a full expert-based exposure assessment.